2008
DOI: 10.1111/j.1540-4560.2008.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

How Adolescents in 27 Countries Understand, Support, and Practice Human Rights

Abstract: An understanding of human rights among young people forms a foundation for future support and practice of rights. We have used data from 88,000 14-year-olds surveyed in the 1999 International Association for the Evaluation of Educational Achievement (IEA) Civic Education Study to examine country differences in students' knowledge pertaining to human rights compared with other forms of civic knowledge, and in students' attitudes toward promoting and practicing human rights. A hierarchical linear modeling (HLM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(91 citation statements)
references
References 26 publications
3
82
1
5
Order By: Relevance
“…In line with previous researchers (e.g. Isac et al 2012;Janmaat 2014;Torney-Purta et al 2008; Torney-Purta and Barber 2011), we acknowledge that several explanatory mechanisms must be taken into account when studying attitudes toward equal rights. We expect that the attitudes of young people toward equal rights may be impacted along different lines and that explanatory variables can be situated at different levels, including, individual background characteristics and experiences (e.g.…”
Section: Explanatory Factorssupporting
confidence: 87%
See 2 more Smart Citations
“…In line with previous researchers (e.g. Isac et al 2012;Janmaat 2014;Torney-Purta et al 2008; Torney-Purta and Barber 2011), we acknowledge that several explanatory mechanisms must be taken into account when studying attitudes toward equal rights. We expect that the attitudes of young people toward equal rights may be impacted along different lines and that explanatory variables can be situated at different levels, including, individual background characteristics and experiences (e.g.…”
Section: Explanatory Factorssupporting
confidence: 87%
“…Isac 2015;Torney-Purta et al 2008) have shown consistent individual differences in political tolerance. Female students, students with more civic knowledge, higher educational expectations and a higher socioeconomic status tend to have more favorable attitudes toward immigrants.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…While 'developmental science has until recently ignored civic engagement, focusing overwhelmingly on cognitive and social development leading to work or family formation' (Sherrod et al 2010: 2), political socialization studies have long neglected political participation outcomes as well (Marsh 1971). Non-cognitive outcomes of school experiences can included attitudes like trust or tolerance, feelings of efficacy, or the intention to participate in civic life (Hahn 1998;Hess 2009;Torney-Purta et al 2008;Westheimer and Kahne 2004). In this article, we focus on a behavioral outcome of school experiences: the intention to participate in different forms of civic and political engagement.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Although these definitions differ slightly, the focus of most definitions is on the possibility to discuss freely and to develop a personal opinion on politics and other issues in class. Previously, open classroom climate has been related to political engagement (Campbell 2008), political trust and interest (Ehman 1980), tolerant attitudes and support for equality (Hahn 1998), gender and politics (Barber and Torney-Purta 2009) and human rights (Torney-Purta et al 2008). …”
Section: Participatory Democratic Climatementioning
confidence: 99%